Толковый словарь русского языка конца ХХ века: языковые изменения / Е. Ю. Ваулина, Т. И. Гайкович, А. В. Зеленин [и др.] ; под редакцией Г. Н. Скляревской - Скляревская Галина Николаевна (Фолио-Пресс, 1998)
Экземпляры: аб. (1999) / Инвентарный номер: 41495 / Цена: / Сис.шифр: 81.2Рус-4 / Авт.знак: Т 52 / ГРНТИ: 16.41.21 / ББК: 81.2Рус-4